Simultaneous isolation and detection of single breast cancer cells using surface-enhanced Raman spectroscopy - Yarbakht, Melina; Nikkhah, Maryam; Moshaii, Ahmad; Weber, Karina; Matthaeus, Christian; Cialla-May, Dana; Popp, Juergen (Talanta, 2018)
Nowadays, cancer is one of the most dangerous and deadly disease all around the world. Cancer that is diagnosed at early stages is more likely to be treated successfully. Treatment of progressed cancer is very difficult, and generally surviving rates are much lower. Therefore, much research has been focused on developing non-invasive methods for detection of cancer and monitoring of its progress. Within this contribution, we present a novel strategy for selective isolation and detection of breast cancer cell lines (MCF-7 and BT-20) based on surface enhanced Raman scattering (SERS). A simplified protocol based on cell-aptamer interaction has been developed in which core-shell (Au@Fe3O4) nanoparticles (CSNs) were functionalized with a mucin 1 (MUC1) specific aptamer (Apt1) to capture cells through the interaction between Apt1 and overexpressed protein (MUC1) on the surface of the tumor cells. Meanwhile, a SERS nano-tag, synthesized by the conjugation of Apt1 to the surface of BSA coated and with 4-mercaptopyridine (4-Mpy) functionalized gold nanoparticles, was used to detect the isolated cells. As a conclusion, the proposed strategy can be extended to isolate and detect cells more precisely based on the detection of different kinds of biomarkers on the surface of cancer cells, simultaneously.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Biomarker; Breast cancer; SERS nano-tag; Surface-enhanced Raman scattering